YSF: A 6TiSCH Scheduling Function Minimizing Latency of Data Gathering in IIoT - Tanaka, Yasuyuki; Minet, Pascale; Vucinic, Malisa; Vilajosana, Xavier; Watteyne, Thomas (IEEE internet of things journal, 2022)
Data gathering systems in the Industrial IoT require an end-to-end latency as low as 1 s with coverage of a few hundred meters. The 6TiSCH standard is well suited for these types of applications. A 6TiSCH network is a multihop wireless IPv6 network which uses time-slotted channel hopping (TSCH). TSCH is a medium access mode of IEEE802.15.4 which provides deterministic properties, and increases robustness against external interference and multipath fading. A key component of TSCH is its scheduling function that builds the communication schedule, which greatly impacts network performance. Although there are several proposed TSCH scheduling solutions in the literature, most of them are not directly applicable to 6TiSCH for real-world deployments because they fail to take into consideration the dynamics of a network. Some of them assume a fixed routing topology, which does not match 6TiSCH where the routing topology dynamically changes with the radio environment. In this article, we propose a full-featured 6TiSCH scheduling function called YSF, that autonomously takes into account all aspects of network dynamics, including the network formation phase and parent switching. YSF aims at minimizing latency and maximizing reliability for data gathering applications. We evaluate YSF by simulation, and compare it to MSF, the state-of-art scheduling function being standardized by the IETF 6TiSCH working group.